Multimodal Assessment of Vascular and Ventricular Function in Children and Adults With Bicuspid Aortic Valve Disease - Weismann, Constance G.; Ljungberg, Sara; Åkesson, Anna; Hlebowicz, J (Frontiers in Cardiovascular Medicine, 2021)
Background: Bicuspid aortic valve (BAV), the most common congenital cardiac anomaly, has been associated with an aortopathy, increased aortic stiffness and diastolic dysfunction. The involved mechanisms and impact of age remain unclear. It was the aim of this study to characterize arterial and cardiac function, their correlation, and the effect of age in children and adults with a history of BAV. Methods: Multimodal cardiovascular assessment included echocardiography, ascending aortic distensibility, common carotid intima media thickness [cIMT], parameters of wave reflection [central (cAIx75) and peripheral (pAIx75) augmentation index corrected to a heart rate of 75/min, aging index (AI)], carotid-femoral pulse wave velocity [cfPWV], and endothelial function (EndoPAT). Multivariable linear regression and correlation analyses were performed. Results: We included 47 BAV patients and 84 controls (age 8–65 years). Ascending aortic stiffness, pulse wave reflection (cAIx75, pAIx75, and AI) and central blood pressure were significantly increased in patients with BAV. However, PWV, cIMT, and endothelial function were not significantly different from controls. BAV patients had marginally reduced diastolic (E': β = −1.5, p < 0.001) but not systolic function compared to controls. Overall, all parameters of arterial stiffness had moderate-strong correlations with diastolic dysfunction and age. In the BAV group, ascending aortic distensibility had the strongest correlation with diastolic dysfunction. Conclusions: BAV is associated with increased proximal arterial stiffness and wave reflection. However, PWV and cIMT are not increased, and endothelial function is preserved. This suggests that the mechanism of arterial and cardiac stiffening is different from patients with acquired heart diseases.